Adult Lysophosphatidic Acid Receptor 1-Deficient Rats with Hyperoxia-Induced Neonatal Chronic Lung Disease Are Protected against Lipopolysaccharide-Induced Acute Lung Injury - Chen, Xueyu; Walther, Frans J.; Laghmani, El H.; Hoogeboom, Annemarie M.; Hogen-Esch, Anne C. B.; van Ark, Ingrid; Folkerts, Gert; Wagenaar, Gerry T. M. (Frontiers in Physiology, 2017)
Aim: Survivors of neonatal chronic lung disease or bronchopulmonary dysplasia (BPD) suffer from compromised lung function and are at high risk for developing lung injury by multiple insults later in life. Because neonatal lysophosphatidic acid receptor-1 (LPAR1)-deficient rats are protected against hyperoxia-induced lung injury, we hypothesize that LPAR1-deficiency may protect adult survivors of BPD from a second hit response against lipopolysaccharides (LPS)-induced lung injury. Methods: Directly after birth, Wistar control and LPAR1-deficient rat pups were exposed to hyperoxia (90%) for 8 days followed by recovery in room air. After 7 weeks, male rats received either LPS (2 mg kg-1) or 0.9% NaCl by intraperitoneal injection. Alveolar development and lung inflammation were investigated by morphometric analysis, IL-6 production, and mRNA expression of cytokines, chemokines, coagulation factors, and an indicator of oxidative stress. Results: LPAR1-deficient and control rats developed hyperoxia-induced neonatal emphysema, which persisted into adulthood, as demonstrated by alveolar enlargement and decreased vessel density. LPAR1-deficiency protected against LPS-induced lung injury. Adult controls with BPD exhibited an exacerbated response towards LPS with an increased expression of pro-inflammatory mRNAs, whereas LPAR1-deficient rats with BPD were less sensitive to this “second hit” with a decreased pulmonary influx of macrophages and neutrophils, interleukin-6 (IL-6) production, and mRNA expression of IL-6, monocyte chemoattractant protein-1, cytokine-induced neutrophil chemoattractant 1, plasminogen activator inhibitor-1 and tissue factor. Conclusion: LPAR1-deficient rats have increased hyperoxia-induced BPD survival rates and, despite the presence of neonatal emphysema, are less sensitive to an aggravated “second hit” than Wistar controls with BPD. Intervening in LPA-LPAR1-dependent signaling may not only have therapeutic potential for neonatal chronic lung disease, but may also protect adult survivors of BPD from sequelae later in life.